2011
DOI: 10.1002/jid.1765
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Development of the Life Insurance Market Affect Economic Growth? Some International Evidence

Abstract: This article investigates the effect of life insurance on economic growth and what conditions affect the insurance-growth nexus. These conditions include the degree of financial development, private saving rates, interest rates, social security expenditures, income, young dependency ratio, life expectancy, and geographic regions. The main findings confirm the positive impact of the development of the life insurance market on economic growth. The insurancegrowth nexus varies across countries with different cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(54 citation statements)
references
References 45 publications
3
48
0
3
Order By: Relevance
“…Lo que representa un posible efecto sustitutivo entre el desarrollo del sector bancario y el sector asegurador, tema que ha sido abordado por otros autores, cabe destacar a Chen et al (2012). Además, se debe poner de manifiesto la necesidad de investigaciones que busquen determinar empíricamente si el desarrollo del mercado asegurador y el desarrollo financiero son sustitutos y, de ser así, a partir de qué nivel de desarrollo financiero.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Lo que representa un posible efecto sustitutivo entre el desarrollo del sector bancario y el sector asegurador, tema que ha sido abordado por otros autores, cabe destacar a Chen et al (2012). Además, se debe poner de manifiesto la necesidad de investigaciones que busquen determinar empíricamente si el desarrollo del mercado asegurador y el desarrollo financiero son sustitutos y, de ser así, a partir de qué nivel de desarrollo financiero.…”
Section: Discussionunclassified
“…Al igual que Chen et al (2012), se establecen las siguientes hipótesis: Las variables fundamentales para el estudio son el crecimiento económico, medido por el crecimiento del PIB real per cápita (cuya fuente es el Banco Mundial) y el ratio de penetración de seguros (para vida, no vida y total), extraído de la base de datos facilitada por la Swiss Reinsurance Company. Además, se incluyen como variables de control el gasto de consumo final del gobierno, la tasa de inflación, el ratio de exportaciones e importaciones sobre el PIB y la inscripción escolar en secundaria (esta última como medida de capital humano), cuya fuente es el Banco Mundial.…”
Section: Especificación Del Modelounclassified
See 1 more Smart Citation
“…Chen Lee & Lee (2012) found that the development of life insurance and the stock market are not complementary but substitute and so we should expect competition of the two variables for investible funds. It is also noted that bank savings account can become a substitute for life insurance policy in an era of uncertainties when customers have a short term The emerging financial institutions from the mergers were thus capacitated for larger ticket deals in the leading sectors of the economy like the oil and gas and telecoms, owning to their new scale, and this may be an impetus for a new wave of mergers.…”
Section: Policies Financial Structures and Non Bank Financial Institmentioning
confidence: 99%
“…58 Brown et al (2000). 59 Chen et al (2011). 60 We also perform the panel cointegration test before the FMOLS estimation of the interactive effect.…”
Section: The Interactive Effect Of Different Dimensions Of Globalisationmentioning
confidence: 99%